Analisis Kualitas Pelayanan Publik Pada Kantor Kecamatan Sukatani Kabupaten Bekasi - Yani, Yani; Syahyuri, Syahyuri (Institut Ilmu Sosial dan Manajemen STIAMI, 2023)
Public service is the State's effort to fulfill the basic needs and civil rights of every citizen regarding goods, services, and administrative services provided by public service providers, it is government. This research aims to know the quality of public services at the Sukatani Sub-district Office in Bekasi Regency of West Java Province. This research employs a descriptive method with a qualitative approach. Data collection techniques involve observation, interviews, and document review with seven informants (sub-district officers). The research findings indicate that the quality of public services at the Sukatani Sub-district Office has not been well-implemented overall, as assessed across five dimensions of public service quality: tangibles, reliability, responsiveness, assurance, and empathy. In terms of tangibles, the waiting area (lobby) lacks amenities such as air conditioning, leading to discomfort for individuals waiting in the space. Regarding reliability, the efficiency of administrative processing by staff is relatively good, evident in their competence and proficiency in utilizing available office technology as a tool to facilitate public service processes. However, responsiveness in serving the public is not fully experienced by the community, as service personnel do not consistently adhere to appropriate timelines, and there are unresolved complaints that have not been promptly addressed. Assurance reveals instances where services remain uncompleted within predetermined timeframes. Additionally, there is evidence of preferential treatment for individuals with familial connections, indicating a lack of empathy in the delivery of public services.